CHALLENGES TO EFFICIENT WATER USE IN AGRICULTURE IN AZERBAIJAN - Gambarova, Ruhiyya; Abbasova, Yegana; Huseynova, Sabina; Maharramov, Shahriyar (Journal of Agricultural Sciences (Belgrade), 2026)
Sustainable food production increasingly depends on water resources and their rational and efficient use. Due to global climate change and desertification, freshwater shortages will become even more acute. Azerbaijan is a country extremely vulnerable to water shortages due to limited internal water resources, high dependence on transboundary rivers, growing climate risks, and the inefficiency of existing water infrastructure. Water scarcity is a key obstacle to agricultural development in the country, and existing irrigation systems are characterised by significant water losses and low efficiency. Given the above, the aim of our study is to identify problems of inefficient water use in agriculture and propose solutions. To assess the level of rational water use in agriculture, we examined indicators such as water withdrawal and consumption, water use for irrigation and agriculture, water losses due to economic activities, the impact of changes in average annual temperature on crop water needs, and the distribution of water resources by region. The results showed that significant water losses pose a serious problem for the agricultural sector and require immediate solutions.